A single center experience on clinical outcomes of vaginoplasty in cloacal anomaly: a retrospective cohort study - Yuyoung Oh; Honam Hwang; Dayoung Ko; Hee-Beom Yang; Joong Kee Youn; Kwanjin Park; Hoon Kim; Ung Sik Jin; Kwi-Won Park; Hyun-Young Kim (Pediatric Surgery International, 2026)
Abstract Purpose This study analyzed the demographics and clinical outcomes of vaginoplasty in patients with cloacal anomaly, focusing on the impact of surgical timing, method, and common channel length. Subgroup analyses evaluated the influence of timing across anatomical categories. Methods We retrospectively reviewed 28 patients who underwent vaginoplasty at Seoul National University Children’s Hospital between 1989 and 2024. Data included associated anomalies, common channel length, timing and method of vaginoplasty, and outcomes related to menstruation, sexual activity, vaginal complications, bowel function, and urinary function. Patients were classified into three groups according to timing of vaginoplasty: Group A (simultaneous with anorectoplasty, n = 21), Group B (separate surgery before age 11, n = 3), and Group C (separate surgery after age 11, n = 4). Group A included both short and long common channel patients. Subgroup analysis was performed based on common channel length (≥ 3 cm vs.